Distribution patterns and enrichment of lead, zinc and copper in surface sediments of the central Portuguese shelf and upper slope - Jesus, C. C.; de Stigter, H.; Miranda, P.; Oliveira, A.; Rocha, F. (Journal of Iberian Geology, 2013)
Geographic patterns of Cu, Pb and Zn enrichment on the Lisbon-Setúbal-Sines continental shelf and upper slope (central Portuguese margin) were studied in this paper to gain insight into current pathways of trace metal dispersal. Our study is based on the analysis of elemental concentrations and mineralogy of surface sediment samples collected offshore one of the most industrialised areas of Portugal. On the Lisbon-Setúbal-Sines shelf concentrations of Al, Fe, Mg, Ti within the fine-grained sediment fraction appear to a large extent related to the amount of fine-grained fraction in the bulk sediment. The extent of enrichment of trace metals in the studied area follows the sequence: Pb > Zn > Cu. Generally, the enrichment of trace metals tends to decrease in offshore direction suggesting that the excess of trace metals must be derived from land. The areas of the Lisbon-Setúbal-Sines shelf most affected by enrichment of trace metals include the Tagus and Sado mud patches and the inner shelf between Tróia and Sines, including the areas close to the Sado outlet and the area adjacent to the St. André and Melides coastal lagoons, which highlights the nearby estuaries and the lagoons as likely sources for the enrichment. In addition, the more widespread enrichment of Pb in sediments points to contributions from atmospheric inputs. The similarity between the results here presented with later data from other authors allows concluding that our results provide a representative view of trace metal enrichment in surface sediments between 1980 and 2000.